Grid to vehicle wireless power supply using single-phase matrix converter - Muhamad Haziq Mohmad Akram; Rahimi Baharom (Institute of Advanced Engineering and Science, 2021)
This paper presents the computer simulation model of a grid to vehicle (G2V) wireless power supply using a single-phase matrix converter (SPMC). The proposed system uses the SPMC that operates as a direct AC-AC converter to convert the supply frequency of 50 Hz to reach 20 kHz output frequency. The use of 20 kHz frequency is suitable for wireless power transfer (WPT) operation in order to obtain higher power transfer efficiency between the transmitter and the receiver parts. An advanced of the proposed circuit topology can solve the conventional system for G2V circuit topology that uses multiple stages of power conversion system, resulting in high power semiconductor losses that could lead to low efficiency. In this work, multiple stages of the conventional